Higher linear algebraic quantum field theory - Bruinsma, Simen (2022)
In this thesis several homotopical aspects of linear algebraic quantum field theory are treated. These homotopical aspects are crucial when formalizing quantum gauge theories in a way that fully respects their gauge symmetries. After preliminaries introducing the relevant elements of category theory, Lorentz geometry, algebraic quantum field theory, chain complexes, model categories and operads, the definition of semi-strict homotopy algebraic quantum field theory is given, weakening only the time-slice axiom.